A THEORY AND PRACTISE IMPROVES TEACHING FOREIGN LANGUAGES: THEORY AND PRACTISE IMPROVES TEACHING FOREIGN LANGUAGES - Xushiyeva, Nargis (Журнал иностранных языков и лингвистики, 2022)
We know, we must have enough knowledge to teach any kind of foreign languages, because teaching foreign languages demands a great responsibility. Especially, nowadays the population of the world is trying to learn a lot of foreign languages, for example: our country gives its great attention to teaching and learning and gives many opportunities, especially for the youth.